AN-AGRIC ANALYSIS ANALYSIS OF MAGNET MEDAN SENSOR MAKING MATERIAL WITH ION IMPLANTATION METHOD - Istiyono, Edi (Jurnal Penelitian Saintek, 2015)
The national instrumental industries need support materials that have good electrical and magnetic properties. One is for sensor to measure magnetic field, i. e.: magnetic layer. The experiment is to find material for magnetic layer that has high GMR ratio requiredfor sensor. The sample is an Ag-Fe thin film produced by ion implantation: silver implanted with iron ions at various doses from 1.5 x 1017 ions/em' to 9.0 x 1017 ions/em' and energy from 40 ke V to 100 ke V GMR is determined by four-point probe method in magneticfield Based on data analysis is conclused that: (1) Increasing of iron ions in Ag-Fe that produced by ion implantation causes decreasing of resistivity. Initially, increasing of annealing temperature causes decreasing of resistivity to minimum point, then the resistivity increases by increasing of annealing temperature; (2) Influence of ions dose, energy and annealing temperature to GMR:' (a) Initially, increasing of iron ions increases GMR ratio to the maximum point, then the GMR ratio decreases, (b) Increasing of the ion energy that is used the GMR ratio produced decreases and (c) Increasing of annealing temperature can rise GMR ratio; (3) Ag-Fe for ion. dose of 6. 0 x 1017 ions/em', energy of 100 ke)', and annealing temperature at 300 'C has a minimum resistivity of (16.7 :f: 3) x 10.9 f2m and optimum of GMR ratio of 6.49%. Ag-Fe in the condition is a good material fot: magneticfield sensor; and (4) the curves of magnetoresistance are simetry and maximum resistance about magneticfield equal to zero.